Toll-Like Receptors in Natural Killer Cells and Their Application for Immunotherapy - Ji-Yoon Noh; Suk Ran Yoon; Tae-Don Kim; Inpyo Choi; Haiyoung Jung (Journal of Immunology Research)
Innate immunity represents the first barrier for host defense against microbial infection. Toll-like receptors (TLRs) are the most well-defined PRRs with respect to PAMP recognition and induction of innate immune responses. They recognize pathogen-associated molecular patterns (PAMPs) and trigger innate immune responses by inducing inflammatory cytokines, chemokines, antigen-presenting molecules, and costimulatory molecules. TLRs are expressed either on the cell surface or within endosomes of innate immune cells. NK cells are one of the innate immune cells and also express TLRs to recognize or respond to PAMPs. TLRs in NK cells induce the innate immune responses against bacterial and viral infections via inducing NK cytotoxicity and cytokine production. In this review, we will discuss the expression and cellular function of TLRs in NK cells and also introduce some therapeutic applications of TLR agonists for NK cell-mediated immunotherapy.